Rancang Bangun Visualisasi Panduan Fitness Berbasis Mobile (Studi Kasus: Atlas Sports Club Surabaya) - Riska Septian Arifiansyah; Teguh Sutanto; Rangsang Purnama (Jurnal Sistem Informasi Universitas Dinamika, 2012)
Weight-bearing exercise (fitness) has now become one of the urban lifestyle in the world, especially in Indonesia. The slogan